2016
DOI: 10.1371/journal.pone.0157268
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Reduces Efficiency of Brain Networks in Subjects with Type 2 Diabetes

Abstract: Previous research has shown that the brain is an important target of diabetic complications. Since brain regions are interconnected to form a large-scale neural network, we investigated whether severe hyperglycemia affects the topology of the brain network in people with type 2 diabetes. Twenty middle-aged (average age: 54 years) individuals with poorly controlled diabetes (HbA1c: 8.9−14.6%, 74−136 mmol/mol) and 20 age-, sex-, and education-matched healthy volunteers were recruited. Graph theoretic network ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 39 publications
3
50
1
Order By: Relevance
“…A short average path length in a WM network facilitates rapid information transfer between different brain regions, which is the basis of cognitive processes . The increased λ in T2DM patients in the present study may reflect disrupted network integration, which is consistent with previous studies on T2DM patients . In T2DM patients, λ was negatively correlated with the ACC of the spatial working memory task, which may reflect that patients with increased λ are worse at dealing with spatial working memory tasks.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…A short average path length in a WM network facilitates rapid information transfer between different brain regions, which is the basis of cognitive processes . The increased λ in T2DM patients in the present study may reflect disrupted network integration, which is consistent with previous studies on T2DM patients . In T2DM patients, λ was negatively correlated with the ACC of the spatial working memory task, which may reflect that patients with increased λ are worse at dealing with spatial working memory tasks.…”
Section: Discussionsupporting
confidence: 89%
“…In T2DM patients, λ was negatively correlated with the ACC of the spatial working memory task, which may reflect that patients with increased λ are worse at dealing with spatial working memory tasks. The changing patterns of clustering coefficients reported in topological network studies on T2DM are not consistent . For example, some studies reported a decreased clustering coefficient in T2DM patients, whereas others reported an increase or no change .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations